If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2s = 12r + 2s Solving 10 + -2s = 12r + 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. 10 + -2s + -2s = 12r + 2s + -2s Combine like terms: -2s + -2s = -4s 10 + -4s = 12r + 2s + -2s Combine like terms: 2s + -2s = 0 10 + -4s = 12r + 0 10 + -4s = 12r Add '-10' to each side of the equation. 10 + -10 + -4s = -10 + 12r Combine like terms: 10 + -10 = 0 0 + -4s = -10 + 12r -4s = -10 + 12r Divide each side by '-4'. s = 2.5 + -3r Simplifying s = 2.5 + -3r
| f(x)=(x-4)(4-x) | | -4(-4+2v)=-20+v | | 3k^2+12k-29=7 | | 1/3x+2/6=5x-2/3 | | (7x+33)=(9x+7) | | 9=2r-5 | | 2x-29=93 | | 23x+5x=2x | | -4(-2x+2)+8x=-(5x+7) | | X-47=12 | | X+3=3+2(2+3x)-5x | | x+x-30=180 | | 6(6x-11)=54x | | b=60+(15+7) | | -5d=20 | | x-30=180 | | (8x-4)+(10x+6)= | | 5x-3=-3x-1 | | (X-7)+12=20 | | 7a-18=-3(-3+3)+7a | | x+15=4x-36 | | -40=b-51 | | H=7+27t-16t^2 | | x*15=4x-36 | | 6(x-11)=54x | | -9r-18r-3r=-12 | | 28=4s+r-s | | 4(3x+3)=3(5x+0.5) | | 1204.2528=2*3.14*6.8*6.8+2*3.14*6.8*h | | 4a-3a=a | | 0=x^2+2x+420 | | 4p+2=-3p+5p |